Hubungan Status Pekerjaan Ibu Dan Pengetahuan Ibu Mengenai Mpasi Terhadap Status Gizi Batita Di Posyandu Sukowidodo 1, 2, Dan 3 Desa Ngargorejo, Boyolali - SUSANTO, DWI, Fitriana Mustikaningrum, S.Gz, M.Sc, Dyah Widowati, SKM (2015)
Introduction : Nutrient status of child under 3 years influenced by direct factors for example intake of foods and infections and indirect factors like mother's work status and mother's knowledge of breastmilk feeding, income, cultural, health service acces, a number of member family,a number of foods, education rate, hygiene and sanitation. Objective : The aim of study was to know the correlation between mother's work status and mother's knowledge of breastmilk feeding with nutrient status of child under 3 years in Posyandu Sukowidodo 1, 2, and 3 Village of Ngargorejo Subdistrict of Ngemplak and District of Boyolali. Research Method : The study use observational method with cross sectional approach and use proportional random sampling to decide minimal sample that will be taken. Total sample in this research amounted 52 subject. Mother's knowledge of breastmilk feeding measured by closed questioner method and nutrient status of child under 3 years measured by antropometric method with index body weight according to age. This index follow WHO standard. Work status of mother measured by seen who are working or not still working. Result : The data figures that more than 80% mothers have a good knowledge of breasmilk feeding, more than 70% mothers are not still working and more than 80% nutrient status of child under 3 years are in normal category. Based on the results of analysis show that there is no relation between moter's work status with nutriens statusof child under3 yeears (the value ρ = 0.338) and there is no relation between mother's knowledge of breastmilk feeding with nutrient status of child under 3 years (the value ρ = 1) Conclusion : There is no relation between mother's work status with nutrient status of child under 3 years and and there is no relation mother's knowledge of breastmilk feeding with nutrient status of child under 3 years.. Keyword : mother's work status, mother's knowledge of associated breastmilk feeding, nutrient status child under 3 years